2022
DOI: 10.1038/s41598-022-16360-7
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and genetic risk factors for chronic Hepatitis B virus infection in a community-based study of 0.5 million Chinese adults

Abstract: Despite universal vaccination of newborns, the prevalence of chronic hepatitis virus B (HBV) infection and the associated disease burden remain high among adults in China. We investigated risk factors for chronic HBV infection in a community-based study of 512,726 individuals aged 30–79 years recruited from ten diverse areas during 2004–2008. Multivariable logistic regression was used to estimate odds ratios (ORs) of hepatitis B surface antigen (HBsAg) positivity recorded at baseline by sociodemographic and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Smoking frequency did not vary much among hepatitis-positive and -negative participants and was found not to be a hepatitis risk factor. A previous study also described smoking to not be related to chronic hepatitis B (33). In our study, utilization of used syringes was found to be associated with hepatitis by X 2 -test but its independent association with hepatitis cannot be recorded by logistic regression analysis.…”
Section: Discussioncontrasting
confidence: 63%
“…Smoking frequency did not vary much among hepatitis-positive and -negative participants and was found not to be a hepatitis risk factor. A previous study also described smoking to not be related to chronic hepatitis B (33). In our study, utilization of used syringes was found to be associated with hepatitis by X 2 -test but its independent association with hepatitis cannot be recorded by logistic regression analysis.…”
Section: Discussioncontrasting
confidence: 63%
“…A recent GWAS with 1943 chronic HBV infection cases and 9571 controls identified a cluster of 450 significant SNPs in the HLA class II region [26], among which rs7770370 was the tagged genetic marker and the A allele was correlated with a significantly lower risk of chronic HBV infections [26]. More recently, a community-based study that enrolled more than 0.5 million adults aged 30-79 years found that the rs7770370 A allele and the rs9277535 A allele were both correlated with significantly lower risks of HBsAg positivity [27]. There is no report regarding the health effects of the rs614348 and rs34039593 polymorphisms, except for their relationships with responses to the HB vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were classified as having chronic HBV infection if their HBsAg test was positive. 20,23…”
Section: Methodsmentioning
confidence: 99%